Florida Trees Store Carbon in Forests and Wood Products - Adam Maggard; Leslie Boby; Martha C. Monroe (EDIS)
Trees store carbon as they grow and produce wood. Carbon, and carbon storage in particular, have become important topics as policymakers, scientists, and industry leaders consider how to address the increasing amount of CO2 in our atmosphere. Because it changes the composition of the atmosphere, CO2 is a leading contributor to climate change. Storing carbon in living trees and in long-lasting wood products such as lumber and furniture is one way to reduce atmospheric CO2. Florida’s forest and wood-product industries are worth billions of dollars. Clean water, wildlife, and other benefits add to the value and importance of these forests.